Intergenerational transmission in Father-Child relationships:: integrative literature review - Brizola Machado, Andriéli de Oliveira (2024)
This integrative review verified, in the literature, the associations between intergenerational transmission and the relationships between father and children in families with children from three to 11 years old. The following databases were consulted: CINAHL, Index Psicologia, LILACS, BDENF, PsycINFO, PubMed, SciELO, SCOPUS and Web of Science. 15 studies were included in this review. There was a predominance in the continuity of positive relationships between generations, that is, men with more involved fathers developed a warmer parenting relationship. To a lesser extent, continuity of distant relationships between parents and children was also observed, and reproduction of physical disciplinary practices between generations. On the other hand, it was also verified, in the studies, the discontinuity of certain models of parental relationship, in an attempt to avoid reproducing conflicting or distant parental relationships.